LEARNING STYLES-UNDERSTANDING FOR LEARNING STRATEGIES: Learning Strategies - Saga, Zarmina; Qamar, Khadija; Trali, Gulshan (Pakistan Armed Forces Medical Journal, 2015)
Objective: To explore the learning preferences of the preclinical students.Place and Duration of Study: Department of Anatomy, Army Medical College from April 2015 to June 2015Study Design: A descriptive study.Material and Methods: Undergraduate students belonging to first and second-year were invited to participate in the exercise. Self-perceived learning style preference was identified. Version 7.8 of the VARK questionnaire in a printed form was used. It consisted of 16 questions with 4 options each. The score for each VARK component of the entire study sample was added up and divided by the total number of study participants to obtain mean scores. A p-value of less than 0.05 was taken as statistically significant.Results: Among 294 students, 153 (52%) unimodal learning style preference was the largest one. Among the unimodal group 34% of the students were auditory learners and 35.9% were kinesthetic learners. Mean scores of individual VARK components based on gender showed no significant difference in terms of unimodal or multimodal learning preferences. More female students compared with male students preferred the A mode (5.32 ± 2.277 versus 5.21 ± 2.767) and the K mode (6.10 ± 2.504 versus 6.05 ± 2).Conclusion: The largest percentage of students with trimodal preferences showed preferences for the auditory and kinesthetic learning strategies.